2020
DOI: 10.1002/jcp.29835
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin promotes β‐cell apoptosis by inhibiting the autophagy of β‐cell via AMPK‐mTOR pathway

Abstract: Asprosin is a newly discovered adipokine. A recent study showed that asprosin promoted the β-cell apoptosis of MIN6 cells. This study aims to determine whether asprosin induces the apoptosis in β-cell via regulating autophagy. Mouse insulinoma MIN6 cells were divided into the following four groups: control, vehicle, high glucose, and asprosin groups. MIN6 cells in the asprosin group were transfected with recombinant asprosin-T2A-GFP vector. MIN6 cells in the vehicle group were transfected with vector only. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Lee et al found that, under hyperlipidemic conditions, pancreatic β-cells release asprosin, elucidating inflammation, cellular dysfunction and apoptosis via toll-like receptor-4 (TLR-4) / c-Jun N-terminal kinase (JNK) phosphorylation, that eventually leading to insulin resistance [ 14 ]. Recently, Wang et al demonstrated that asprosin induces apoptosis of β-cells by inhibiting their autophagy via adenosine monophosphate-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling pathway [ 49 ]. Moreover, in C2C12 myocytes, asprosin treatment augmented insulin resistance by impairing insulin receptor substrate (IRS)-1 and Akt phosphorylation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that, under hyperlipidemic conditions, pancreatic β-cells release asprosin, elucidating inflammation, cellular dysfunction and apoptosis via toll-like receptor-4 (TLR-4) / c-Jun N-terminal kinase (JNK) phosphorylation, that eventually leading to insulin resistance [ 14 ]. Recently, Wang et al demonstrated that asprosin induces apoptosis of β-cells by inhibiting their autophagy via adenosine monophosphate-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling pathway [ 49 ]. Moreover, in C2C12 myocytes, asprosin treatment augmented insulin resistance by impairing insulin receptor substrate (IRS)-1 and Akt phosphorylation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, for example, promotes FAO by activating the expression of PPARα and ACOX1 [107,108], whereas mTOR promotes the accumulation of FAs by shutting down β-oxidation [109,110]. Hence, these are considered the AMPK-mTOR pathway for regulating β-oxidation [111]. The NAD-dependent protein lysine deacylases of the sirtuin family regulate various physiological functions, from energy metabolism to stress responses [112].…”
Section: Othersmentioning
confidence: 99%
“…[ 13 ] It is also observed that asprosin could argument the inflammation response, feeding regulation, cellular dysfunction, and apoptosis. [ 14–16 ] It is worth noting that there is a significant increase in asprosin levels in pregnant women with gestational diabetes and their offspring. [ 17,18 ] However, contradictory findings regarding the expression level of asprosin have been observed, with some studies showing asprosin increased in children with obesity and associated with insulin resistance, [ 19,20 ] and others showing asprosin decreased in children with obesity.…”
Section: Introductionmentioning
confidence: 99%